Surface plasmon enhanced thermal properties of noble metallic nanofluids - Lee, Kwang Hong (2011)
We explore here the possible contribution of surface optical properties to the thermal properties of metallic nanofluids. During temperature ramping of a gold nanofluid model system, measured Surface Plasmon Resonance (SPR) is found to correlate with Thermal Conductivity Enhancement (TCE) of the nanofluid. The depth of the SPR dip in reflectivity spectrum is indicative of the strength of excited SPR and this varies proportionally with the temperature of the nanofluid. With an increase in temperature, the SPR strength increases with a corresponding increase in the TCE. However, when the strength of the resonance starts to decrease, the TCE starts to increase at a decreasing rate. This correlation of SPR to TCE is the strongest in nanofluids with a low concentration of nanoparticles. This mechanism of thermal enhancement is most likely attributable to the high surface area to volume ratio of the nanoparticles, and should be operative in other metallic nanoparticle suspensions as well.